2019
DOI: 10.31002/metathesis.v3i2.1921
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media for English Language Learning: An Exploratory Study of Efl University Students

Abstract: This study aims to examine the use of social media in English language learning by the students of English Study Program at Jambi University. This study applied an exploratory study to investigate the use of social media for English language learning. The researcher employed a survey and semi-structured interview in collecting the data. Sixty-seven students participated to answer the questionnaire and ten participants were interviewed, randomly selected from participants who answered the questionnaire. Basic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Numerous studies published have posited that the utilization of social media can help increase English language learners' English proficiency. Zam Zam Al Arif [48] posited that EFL learners showcase positive attitudes towards the utilization of social media in English language learning which can help increase their motivation and willingness in English language speaking and acquisition. Previous studies have also indicated that most of the EFL learners believed that the utilization of social media integrated with short videos can help improve their English communication competence acquisition via self-regulated learning mode with the popular topics shared by English educators [42,39,49].…”
Section: Previous Research On the Application Of Social Media In English Language Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies published have posited that the utilization of social media can help increase English language learners' English proficiency. Zam Zam Al Arif [48] posited that EFL learners showcase positive attitudes towards the utilization of social media in English language learning which can help increase their motivation and willingness in English language speaking and acquisition. Previous studies have also indicated that most of the EFL learners believed that the utilization of social media integrated with short videos can help improve their English communication competence acquisition via self-regulated learning mode with the popular topics shared by English educators [42,39,49].…”
Section: Previous Research On the Application Of Social Media In English Language Communicationmentioning
confidence: 99%
“…Meanwhile, students can also create their own digital oral English presentations in the form of short videos in TikTok. In this case, teachers as well as some other TikTok users can give comments to help improve these cohort of students' English communication competence by giving comments [48].So EFL learners who use TikTok could acquire English language communication competence via these short videos in English without the limitations of space An Overview of the Utilization of TikTok to Improve Oral English Communication Competence among EFL Undergraduate Students and time [10].Another advantage of the utilization of TIKTOK mobile applications in English education is the length of each video, which is only fifteen seconds contributing to make its excellence in short attention span, and helping EFL youngsters to get the point of the knowledge as well as focus on learning English language communication knowledge effectively.…”
Section: Previous Research On the Application Of Social Media In English Language Communicationmentioning
confidence: 99%
“…Technology, for instance, personal computer, mobile phone and the internet are considered as effective tools to support the teaching and learning process. The technological advances have had such a great impact on the field of education especially in learning English as a foreign language (Zam Zam Al Arif, 2019). But, in fact, most teachers have not utilized the technology optimally yet in teaching the English language.…”
Section: Introductionmentioning
confidence: 99%
“…Another informant from the Philippines said that the function is to contact friends, relatives, and classmates, as the informant is the head of the class; others suggested that it can also increase knowledge, especially by watching educational documentation through videos on YouTube. On the contrary, the research conducted by (Al Arif, 2019) and indicated that a range of social media, especially Instagram and Facebook, are used by students. The research also suggested that social media (six popular social media, i.e., Facebook, WhatsApp, Snapchat, Instagram, Telegram, and Twitter) are perceived as tools for learning English as a foreign language.…”
Section: Resultsmentioning
confidence: 96%